Isokinetic performance of knee extensors and flexor muscles in adolescent basketball players - Viçosa Bonetti, L.; Piazza, F.; Marini, C.; Soldatelli Zardo, B.; Saciloto Tadiello, G. (Archivos de medicina del deporte, 2017)
Background: Basketball is one of the most popular and most practiced sports in the world, being played by 450 million people worldwide, and the knee is the most commonly injured region of the body involving adolescent male basketball players. Isokinetic dynamometry is generally considered the best protocol for dynamic strength measurements, which are important for preventing musculoskeletal injuries. Therefore, the objective of the present study was to analyze the muscular performance, the unilateral differences and relationships between the knee extensor and flexor muscles in adolescent male basketball players.